(untitled) (Fiep Bulletin - online, 2017)
This article is one unfolding of a research carried out by researchers from UNIVALI for FAPESC about theMore Medical Doctors Program (PMM). It also utilizes as source, the dissertation by Rafael Celi titled Thinking Styles in PhysicalEducation in the SUS Context. It has the objective of making a double contribution: for the insertion of physical educationprofessionals in the NASF (this way, aiming at the PMM integrality) and with an epistemology to think on the insertion of suchprofessionals in the SUS. The utilized method comprised a bibliographic review of 55 articles from 5 Brazilian books that connectphysical education with health and an analysis in the light of the Thinking Styles (EP) in Public Health, fruits of a doctorate thesisby Marco Da Ros. It has been found 10 different EPs which can be grouped into 2 macro-trends. One macro-trend contemplatesPublic Health that gathers 4 EPs: Normative Planning, Sanitary Education, Classic Epidemiology and Preventive Medicine. Theother regards Collective Health with 5 EPs: Strategic Planning, Health Education, Critical Epidemiology, Society andDiscriminated Social Segments, and Epistemology in Health.